Epidemiological Profile of Herpes Zoster and Its Association with Comorbidities in Al-Nasiriyah, Iraq - Ali, Alyaa Mousa; Abid, Intidhaar Naeem; Rhadi, Sabah Hasan (Medical Science Journal for Advance Research, 2026)
Background: Herpes zoster (HZ), resulting from the reactivation of the varicella-zoster virus (VZV), is a significant cause of morbidity. Understanding its local epidemiology and association with comorbidities is crucial for public health planning. Objective: This study aimed to investigate the demographic characteristics and prevalence of comorbid conditions among patients with HZ in Al-Nasiriyah, Iraq. Materials and Methods: A retrospective, cross-sectional study was carried out through the medical records of 132 HZ patients at al-Hussain Teaching Hospital. Demographic patient characteristics, clinical presentation, history of varicella and comorbidities (eg diabetes mellitus and hypertension) were evaluated. Results: A total of 132 (86 males, 65.2% and 46 females, 34.8%) definite intellectual disability (ID) patients were included in the study. The greatest disease prevalence (34.1%) pertained to patients older than 50 years old. Most of them (71.2%) mentioned previous varicella infection. Comorbidities were frequent and hypertension was found in 15.1% of cases, followed by diabetes mellitus in 10.6%. Those comorbidities were mostly detected for people over 50 years of age (respectively, 60.0% and 57.1% in hypertension and diabetes cases within the HZ cohort). Conclusion: Herpes zoster occurs primarily in the elderly of this Iraqi population and is strongly correlated with systemic diseases including hypertension and diabetes mellitus. These data demonstrate the utility of HZ as a potential marker for underlying chronic diseases and provide rationale for increased surveillance and vaccine approaches to high-risk children.